PROBLEM BASED COOPERATIVE LEARNING AND ITS POTENTIAL IN ENHANCING LANGUAGE LEARNERS HIGHER ORDER THINKING SKILLS (HOTS) - Syafini Ismail; TNRTM Maasum; Norkhairi Ahmad (Universitas Duta Bangsa Surakarta, 2022)
This qualitative study investigated the language learning strategies adopted by students whom developed higher order thinking skills (HOTS) via Cooperative Problem- based learning (CPBL) activities in the writing class. The objective of the study is to investigate how language learning strategies in writing lessons adopted by the students develop their higher order thinking skills in the CPBL ESL writing classroom. This study further explored the language learning strategies that students adopted in order to complete writing tasks which require them to exercise their higher order thinking skills. The study was conducted on 13 secondary level form 4 students from an urban school where the collection of data was via structured reflective journal and teacher interviews. The study revealed that the language learning strategies in writing that developed higher order thinking skills within the students were cognitive and compensation strategies while the indirect strategies are cognitive and social strategies. These language learning strategies in writing developed the higher order thinking skills of analysing, evaluating and creating. This study also provided insights on the strategies that English teachers should focus on in the writing classroom via implementation of problem based cooperative learning activities to develop students higher order thinking skills among their students.